EST-SSR Primer Development and Genetic Structure Analysis of Psathyrostachys juncea Nevski - Li, Zhen; Yun, Lan; Gao, Zhiqi; Wang, Tian; Ren, Xiaomin; Zhao, Yan (Frontiers in Plant Science, 2022)
Psathyrostachys juncea is a perennial forage grass which plays an important role in soil and water conservation and ecological maintenance in cold and dry areas of temperate regions. P. juncea has a variety of biotic and abiotic stress tolerance related genes that have been used in crop improvement, indicating its agronomic, economic, forage and breeding value. To date, there have been few studies on the genetic structure of P. juncea. Here, the genetic diversity and population structure of P. junca were analyzed by EST-SSR molecular markers to evaluate the genetic differentiation related to tillering traits in P. juncea germplasm resources. The results showed that 400 SSR loci were detected in 2,020 differentially expressed tillering related genes. A total of 344 scored bands were amplified using 103 primer pairs, out of which 308 (89.53%) were polymorphic. The Nei's gene diversity of 480 individuals was between 0.092 and 0.449, and the genetic similarity coefficient was between 0.5008 and 0.9111, with an average of 0.6618. AMOVA analysis showed that 93% of the variance was due to differences within the population, and the remaining 7% was due to differences among populations. P. juncea materials were clustered into five groups based on population genetic structure, PCoA and UPGMA analysis. The results were similar between clustering methods, but a few individual plants were distributed differently by the three models. The clustering results, gene diversity and genetic similarity coefficients showed that the overall genetic relationship of P. juncea individuals was relatively close. A Mantel test, UPGMA and structural analysis also showed a significant correlation between genetic relationship and geographical distribution. These results provide references for future breeding programs, genetic improvement and core germplasm collection of P. juncea.